A new species of Bauhinia (Cercidoideae, Leguminosae) from the states of Pernambuco and Alagoas, Brazil - Santos, Antonio C.b. Dos; Vaz, Angela M. Studart Da F.; Silva, Maria A.p. Da; Paula, Antonio P.o.; Feitoza, Lidiane De L.; Carvalho, Reginaldo De (Phytotaxa, 2022)
Bauhinia andrade-limae is a new species of Leguminosae endemic to the Atlantic Forest domain, occurring in the states of Alagoas and Pernambuco in northeastern Brazil. The new species is morphologically similar to Bauhinia membranacea, both sharing largely ovate bilobed leaves with an obtuse apex, generally with nine main veins and lenticulate stems. B. andrade-limae differs from B. membranacea by the chartaceous leaves with a cordate base and congested lobes in at least 1/3 of the total length, upper and lower sides glabrous; flower buds up to 5.3 cm long in anthesis and glabrous, reticulate legume with woody valves. A detailed description with distribution, photographs and an illustration of the new species is provided.